Master of Arts in Economics - Kabale University (2022)
This programme is conceptualized around the Government’s Vision 2040 and aligns very well with the priorities of the National Development Plan II (NDP II) that seeks to strengthen the fundamentals of the economy through harnessing the abundant opportunities in its various sectors. It is intended to develop and educate the future leaders, managers and strategic thinkers both in public and private institutions with economics knowledge and expertise. It also aims at boosting competency and experts in managerial, advisory and academic positions in the in the economics discipline; offering solid training in economics; and will give a deeper understanding of the complexity of economic transformations necessary to transit countries like Uganda, the region and Africa to industrialized and modern economy status.